Antibacterial Potential of Jatropha sp. Latex against Multidrug-Resistant Bacteria - Muhammad Evy Prastiyanto; Prayoda Deri Tama; Ninda Ananda; Wildiani Wilson; Ana Hidayati Mukaromah (International Journal of Microbiology)
Objective. This study was aimed to evaluate the antibacterial activity of the latex of three species members of Jatropha (J. curcas, J. gossypilofia Linn., and J. multifida) against methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase- (ESBL-) producing Escherichia coli and ESBL-producing Klebsiella pneumonia, carbapenemase-resistant Enterobacteriaceae (CRE)-E. coli, K. pneumoniae-carbapenemase (KPC), and carbapenemase-resistant Pseudomonas aeruginosa (CRPA). Method. The antibacterial activities were calculated based on the inhibition zones using the Mueller–Hinton agar diffusion method, minimum inhibitory concentration (MIC) using Mueller–Hinton broth in a microdilution method, and minimum bactericidal concentration (MBC) using blood agar plate. Results. The latex of Jatropha showed antibacterial activities against the MRSA and CRPA. All latex of Jatropha appeared to have the antibacterial activities against MRSA and CRPA in the diffusion method (20.4–23.7 mm and 12–15 mm), MIC (0.19–6.25%, and 25%), and MBC (0.39–12.5% and 50%). Phytochemical screening of latex indicated the presence of flavonoids. Conclusions. The latex of J. curcas, J. gossypilofia Linn., and J. multifida has the potential to be developed as antibacterial agents, especially against MRSA and CRPA strain, but further in vivo research and discovery of the mode of its action are required to shed the light on the effects.